Anxiety and depression symptoms among women attending group-based patient education courses for hereditary breast and ovarian cancer. Issue 1 (December 2017) - Listøl, Wenche; Høberg-Vetti, Hildegunn; Eide, Geir; Bjorvatn, Cathrine
Abstract Background Women carryingBRCA -mutations are facing significant challenges, including decision making regarding surveillance and risk-reducing surgery. They often report that they are left alone with these important decisions. In order to enhance the genetic counselling session we organized a group-based patient education (GPE) course for women withBRCA -mutations. The study aims were to characterize women attending a group-based patient education (GPE) course for hereditary breast and ovarian cancer, consider the usefulness of the course, evaluate symptoms of anxiety and depression among the participants, and finally investigate whether their levels of anxiety and depression changed from before to after the course session. Methods A prospective study was conducted. Two weeks before (T1) and 2 weeks after (T2) attending the GPE-course the participants received questionnaires by mail. We collected information on demographic- and medical variables, anxiety and depression using Hospital Anxiety and Depression Scale (HADS), self-efficacy using The Bergen Genetic Counseling Self-Efficacy scale (BGCSES) and coping style using the Threatening Medical Situations Inventory (TMSI). A total ofN  = 100 (77% response rate) women participated at baseline and 75 (58% response rate) also completed post-course assessment. Results The mean level of anxiety symptoms was elevated among participants but decreased significantly during follow-up. Lower anxiety symptom levels were associated with "longer time since disclosure of gene test result", "higher levels of self-efficacy" and having experienced "loss of a close relative due to breast or ovarian cancer". Lower depression symptom levels were associated with "higher levels of education" and "loss of a close relative due to breast or ovarian cancer". Conclusion The women in this study seemed to benefit from the GPE course. Women newly diagnosed with aBRCA mutation who reported lower levels of self-efficacy and lower levels of education were more vulnerable. These women need special attention.